Nanocurcumin Innovation as an Anti-Apoptosis of Ovarian Granulosa Cells in White Rats Exposed to Lead Acetate (PbAc) - Anis Satus Syarifah (Babali Nursing Research, 2022)
Introduction: Exposure to Pb causes increased apoptosis of ovarian granulosa cells through oxidative stress mechanism. Curcumin has protective effects on reproductive organs, anti-apoptotic, antioxidant in normal cells. Curcumin in innovated nano form can function as an effective anti-apoptosis in ovarian granulosa cells of rats due to PbAc exposure. Methods: Thirty female rats were divided into 3 groups, the negative control group (the rats receiving distilled water, in each 90 minutes receiving corn oil), positive control group (the rats receiving PbAc of 30 mg/kg BW, in each 90 minutes receiving corn oil), the experimental group, in which the rats receiving PbAc of 30 mg/kg BW, and in each 90 minutes receiving nanocurcumin of 200 mg/kg BW. All groups received treatment orally once a day for 30 days. On day 31 the rats to granulosa cell apoptosis examination using Tunnel method. Results: Rate of apoptosis was in the positive control group (5.4 ± 0.8%/micro) and the lowest was in the experimental group (1.1 ± 0.5%/micro) and the negative control group (1.2 ± 0.6). The experimental group showed the same p value as the negative control group (p = .095) and different p value (p = .010) from the positive control group. These findings indicated that the innovation of curcumin in nano form at a dose of 200 mg/KgBW reduced apoptosis of rat ovarian granulosa cells due to PbAc exposure. Conclusion: The innovation of curcumin in nano form has the potential as an effective natural anti-apoptosis in rats ovarian granulosa cells exposed to PbAc.